The impact of virtual environment on physiological reactivity and perceived physiological arousal among students with public speaking anxiety and the mediating role of safety behaviors - Karen Kristinsdóttir 1995- (2019)
The overarching goals of the present study were to examine whether individuals with high levels of public speaking anxiety (PSA) would demonstrate higher physiological reactivity and perceive higher physiological arousal to public speaking in a virtual reality (VR) environment than individuals with low PSA levels and whether this relationship would be mediated by safety behaviors. The sample in this study consisted of 81 students at Reykjavik University (62 females and 19 males), median-split into two groups (high vs. low PSA). Participants delivered an impromptu speech in front of a virtual reality audience while physiological reactivity was assessed using heart-rate variability. Perceived physiological arousal as well as public speaking anxiety in the virtual environment were assessed with self-report questionnaires. No group difference based on the subjects’ PSA levels was found on physiological reactivity measures in the VR environment. However, those with high PSA levels perceived greater physiological arousal in the virtual environment and the relationship was shown to be mediated by safety behaviors. In addition, participants felt immersed in the VR environment, as both PSA levels reported equally high levels of presence. Future studies and clinical implications of these findings in treatment of PSA are discussed. Helsta markmið rannsóknarinnar var að kanna hvort einstaklingar með mikinn framkomukvíða sýndu aukna lífeðlislega virkni og meiri upplifun af líkamlegum einkennum á meðan þeir fluttu ræðu fyrir hópi áhorfenda í sýndarveruleika, samanborið við þá sem óttast minna að koma fram. Auk þess var skoðað hvort sambandi þessara þátta væri miðlað af þeirri öryggishegðun sem einstaklingar nýta sér almennt í kvíðvænlegum aðstæðum. Úrtakið samanstóð af 81 nemanda við Háskólann í Reykjavík (62 konur og 19 karlar), sem skipt var í tvo hópa út frá miðgildi kvarða sem metur framkomuótta. Þátttakendur fluttu óundirbúna ræðu fyrir hópi áhorfenda í sýndarveruleika og var lífeðlisleg virkni þeirra mæld í gegnum ...